Live birth by cesarean section after rupture of uterine cornua in simultaneous corneal and intrauterine pregnancies. Issue 8 (9th May 2021) - Banzai, Chiaki; Hiraishi, Hikaru; Higeta, Daisuke; Tsukagoshi, Noriko; Murata, Tomomi; Soda, Masayuki
Abstract: A patient became pregnant by in vitro fertilization and embryo transfer (IVF‐ET). She had a history of laparoscopic bilateral salpingectomy and enucleation of a left ovarian tumor due to bilateral hydrosalpinx and left endometriotic cyst in primary infertility. She noticed abdominal pain and visited the nearby general hospital by ambulance (gestational age 6 weeks and 1 day). She was admitted to our department because of ascites. An abdominal hemorrhage due to a rupture of the residual corneal segment of the fallopian tube was suspected and emergency laparoscopic surgery was performed. Simultaneous internal and external pregnancy resulted in rupture of the right tubal corneal at the ectopic site of pregnancy. The baby in the uterus grew smoothly and was delivered by cesarean section. This is a report of a case in which live birth after rupture of uterine cornua in simultaneous corneal and intrauterine pregnancies. We searched the literature for similar cases and examined management methods.